2020
DOI: 10.23960/jesr.v2i1.44
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Visual Abilities in Solving Mathematics Problems

Abstract: This research is an experiment of categorizing visual abilities by representations of a solving problem through class experiment. The research is to investigate, explore, and enhance geometry thinking in solving mathematics problems presented visually. The tasks are cognitive strategies that rely on the visual representations and the genesis of the abilities with the assumption that the performance requires the manipulation of the visual representations. The model of the research developed from the students’ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…There are three phases in unfolding the practical of numerical literacy, i.e., formative, mathematical, and integrative. These are in a framework of the development that showed the level of numeracy concept [23]. The levels were analyzed statistically according to the phases.…”
Section: Methodsmentioning
confidence: 99%
“…There are three phases in unfolding the practical of numerical literacy, i.e., formative, mathematical, and integrative. These are in a framework of the development that showed the level of numeracy concept [23]. The levels were analyzed statistically according to the phases.…”
Section: Methodsmentioning
confidence: 99%
“…The current target of implementing mathematics education emphasizes the importance of developing understanding/understanding skills and critical, creative, and productive thinking skills, especially for prospective secondary school teachers. In line with that, several national reports in various countries have shown that instructional design to stimulate thought processes and problem-solving and generate complex solutions is urgently needed (Halpern, 2013;King et al, 2003;Moseley et al, 2005;Rif'at & Fitriawan, 2020;Wallbank, n.d.;Zohar et al, 2001) so that students can adapt to any changes (Halpern, 2013), acquire new knowledge more quickly and be able to face the complexities of real problems in life (Conklin, 2012;King et al, 2003;Sumar & Sumar, 2020). This will be achieved if students at the primary and secondary levels begin to be fostered or trained to develop such a mindset.…”
Section: Introductionmentioning
confidence: 90%